Analisis Resolusi Konflik Pemerintah Daerah Banyuwangi terhadap Konflik Rumah Ibadah Berbasis Kerifan Lokal - Juwono, Hendro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
Conflict can happen to everything in diversity. Existing differences have the potential to trigger conflict. Conflicts can be avoided and can also be arranged in such a way as not to level up. Among the handling of conflicts can be resolution through local wisdom. This paper tries to describe the results of local government conflict resolution analysis in conflict resolution based on local wisdom. The research method uses qualitative with a literature study approach. The results of the research, the local government has succeeded in conducting dialogue on various conflicts that occurred in the Banyuwangi area. The village government as the government is most in touch with the community and knows best the condition of the community's character is considered capable of resolving village-level conflicts. Conflict resolution in the village uses resolution based on local wisdom. Community leaders as the main center function as referees who do not take sides with two interested parties, as well as provide input and direction, as well as joint solutions to the problems faced.